On Constitutional Ground - Ely, John Hart, 1938-2003 (Book collections on Project MUSE., 1996)
John Hart Ely is a leading contemporary writer on political theory from the standpoint of American constitutional law. This collection covers a full range of topics of constitutional interpretation: federalism, separation of powers, freedom of expression, religious freedom, criminal procedure, racial discrimination, ""substantive due process,"" and honesty in government. Organized under these heads and linked by the author's witty explanatory and autobiographical remarks, the essays and other documents--many previously unpublished in any forum--range chronologically over the past three deca.